2021
DOI: 10.1038/s41598-021-90653-1
|View full text |Cite
|
Sign up to set email alerts
|

Totipotency of mouse zygotes extends to single blastomeres of embryos at the four-cell stage

Abstract: In multicellular organisms, oocytes and sperm undergo fusion during fertilization and the resulting zygote gives rise to a new individual. The ability of zygotes to produce a fully formed individual from a single cell when placed in a supportive environment is known as totipotency. Given that totipotent cells are the source of all multicellular organisms, a better understanding of totipotency may have a wide-ranging impact on biology. The precise delineation of totipotent cells in mammals has remained elusive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…We found that the initial slight dissimilarity between early twin blastocysts increased as their development progressed, and at the late blastocyst stage, not only did the proportion of EPI cells differ but also the total number of cells, the number and fraction of TE cells, and the percentage of PE cells. This finding is consistent with the results of Maemura et al, who demonstrated that only 13% of 2-cell embryo blastomeres were able to form PE and EPI cell lineages in the ICM 55 . Similarly, Lorthongpanich et al .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that the initial slight dissimilarity between early twin blastocysts increased as their development progressed, and at the late blastocyst stage, not only did the proportion of EPI cells differ but also the total number of cells, the number and fraction of TE cells, and the percentage of PE cells. This finding is consistent with the results of Maemura et al, who demonstrated that only 13% of 2-cell embryo blastomeres were able to form PE and EPI cell lineages in the ICM 55 . Similarly, Lorthongpanich et al .…”
Section: Discussionsupporting
confidence: 93%
“…Monozygotic twins resulting from the development of two separated sister blastomeres are rarely born, indicating an unequal developmental potential of blastomeres of the 2-cell embryo 4 – 9 . This observation does not contradict the totipotency of the 2-cell mouse embryo blastomeres, but suggests uneven developmental potential of the cells emerging from the first cleavage division 8 , 9 , 54 , 55 .…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations